Sínteses e caracterizações de sílicas mesoporosas funcionalizadas para detecção eletroquímica de Cu2+ em cachaça - Lima, Jéssica Brito dos Santos (2017)
In this work, three methods of synthesis were proposed for formation of mesoporous material type MCM-41 functionalized with aminopropyltrimethoxisylane (APTS) by direct (in situ) and indirect (after synthesis) routes. The FTIR spectra showed characteristic vibrations referring to the connections of silica mesostructures of kind MCM-41. The materials obtained presented adsorption and desorption isotherms of type IV N2, exhibited properties of mesoporous materials according to IUPAC classification. The Xray diffractograms of MCM-41 (R1a) and MCM-NH2 (R1b) showed a hexagonal structure according to a presence of reflection planes (100), (110) and (200), already for the mesoporous functionalized in situ (R2 and R3), this behavior was not observed. The thermal stability of the materials was verify from the TG curves. Subsequently, carbon paste electrodes (EPC) and chemically modified electrodes (EPCMs) were prepared by immobilizing the synthesized materials for applications in Cu2+ detection. The modified electrode obtained by immobilization of functionalized mesoporous R2 (EPCM / R2), presented better sensitivity for the detection of copper ions. The use of 10% in the paste composition at pH 6.0, applying -0.5 V (vs. Ag / AgCl) during 600 s preconcentration and 10 mV s-1 scanning speed favored the analytical signal in terms of intensity and resolution. The method presented a linear range of 0.99 to 11.80 μmol L-1 (R2 = 0.994), sensitivity (LD=0.16 μmol L-1; LQ=0.48 μmol L- 1), precision (DPRmáx = 10.62%), accuracy (92.24%) e selectivity in the presence Zn2+, Cd2+, Fe2+, Mn2+, Pb2+ satisfactory. The method developed proved to be efficient for monitoring Cu2+ in sugar cane liquor, presenting content comparable to that obtained by AAS. The analyzed sugar cane liquor showed amount of Cu2+ within the limit established by legislation.